'IAPAR 8 - Rio Negro', a new bean cultivar - Alberini, João Luiz; Mohan, Suryadevara K.; Menezes, José R. de; Silva, Walter Rodrigues da; Oliari, Lourenço; Meyer, Rolfi C. (Pesquisa Agropecuaria Brasileira, 2014)
After five cycles of selection under field conditions, a new bean (Phaseolus vulgaris L.) cultivar was obtained, ‘IAPAR 8 - Rio Negro', which has black seed coat, upright growth habit, 92 days from emergence to maturity, and field resistance to all physiological races of the fungus Colletotrichum lindemuthianum known to the moment. Its 1000 seeds weight is around 210 g, it shows wide adaptation, and yields 3000 kg/ha under good edaphic and climatic conditions. Yield data of the new cultivar, obtained from three different localities in the state of Paraná, Brazil, and its main characteristics are presented.